Thioredoxin-interacting protein: A new therapeutic target in bone metabolism disorders? - Jiang, Na; Liu, Jinjin; Guan, Conghui; Ma, Chengxu; An, Jinyang; Tang, Xulei (Frontiers in Immunology, 2022)
Abstract Abstract For developing novel therapeutic strategies, target identification in diseases is essential. Thioredoxin-interacting protein (TXNIP), also known as thioredoxin-binding protein-2 (TBP-2), is a member of the α-arrestin protein family regulated by several cellular stress factors. Overexpression of TXNIP coupled with thioredoxin (TRX) inhibits its antioxidant function, thereby increasing oxidative stress. TXNIP is directly involved in inflammatory activation by interacting with the Nod-like receptor protein 3 (NLRP3) inflammasome. Bone metabolic disorders are associated with aging, oxidative stress, and inflammation and are characterized by an imbalance between bone formation involving osteoblasts (OBs) and bone resorption by osteoclasts (OCs), and by chondrocytes (CCs) destruction. The role of TXNIP in bone metabolic diseases has been extensively investigated. Here, we discuss the role of TXNIP in the regulatory mechanism of transcription and protein levels and summarize its involvement in bone metabolic disorder diseases such as osteoporosis (OP), osteoarthritis (OA), and rheumatoid arthritis (RA). TXNIP is expressed in osteoblasts, osteoclasts, and chondrocytes and affects the differentiation and function of skeletal cells through both redox-dependent and independent regulatory mechanisms. Therefore, TXNIP is a potential regulatory and functional factor in bone metabolism and a possible new target for the treatment of bone metabolism-related diseases.